ADDITIONAL CRIMINAL SANCTIONS AGAINST CORRUPTION CRIMES IN INDONESIA - Purnama, Chandra (Proceeding International Seminar of Islamic Studies, 2023)
One of the phenomenal crimes today is corruption. This crime is not only detrimental to state finances, but is also a violation of the social and economic rights of the people. Corruption has destroyed the foundations of religion, moral and ethical values. Additional Criminal Sanctions against corruption in the form of confiscation of tangible or intangible movable property or immovable property used for or obtained from corruption, including companies owned by the convicted person where the criminal act of corruption was committed, as well as goods that replace goods - the goods, payment of replacement money in the same amount as the corrupted property, closure of all or part of the company for a maximum period of 1 (one) year and revocation of all or part of certain rights or elimination of all or part of certain profits, which have been or can be given by the Government to the convict.